Experimental study on mechanical properties of steel under extreme cyclic loading considering pitting damage. (15th August 2019) - Ma, Houbiao; Yang, Yang; He, Zheng; Zhang, Yahui; Ji, Fei
Abstract: Extreme cyclic loading and pitting are unavoidable damage factors for steel offshore platforms. The degradation of mechanical properties of steel caused by such double damage cannot be obtained by a simple addition of degradation caused by a single damage. In order to analyze the above problems, the high-strength steel NV-D36 commonly used in offshore platforms, was selected as an experimental specimen. Different degrees of pitting damage were generated by laboratory electrochemical accelerated corrosion. Seven typical cyclic loading programs were designed based on the real extreme cyclic loads that offshore platform may be subjected to. The cyclic loads were applied to the specimens to obtain the hysteretic properties of healthy and pitting specimen. Under cyclic loading, the stiffness and the strength of steel were strengthened, in contrast, pitting damage could cause local volume loss and local stress concentration, which result in degradation of stiffness and strength of steel. Generalized yield strength and generalized Young's modulus of steel were gradually degraded with the deepening of pitting damage. The cyclic hardening coefficient linearly degenerated with the pitting volume loss rate, and the degree of degradation was almost irrelevant to the cyclic loading program. The cyclic hardening exponent was almost unaffected by pitting damage. Highlights: Different degrees of pitting specimen were generated by laboratory electrochemical accelerated corrosion. Different cyclic loads were applied to the specimens to obtain the hysteretic properties of healthy and pitting specimen. The deterioration law of mechanical properties of the steel with double damage was analyzed.